Odpowiedź :
a)
[tex]-(\frac{5}{6} + \frac{1}{3}) : (2\frac{2}{3} - 1\frac{3}{4}) = -(\frac{5}{6} + \frac{2}{6}) : (\frac{8}{3} - \frac{7}{4} ) = -\frac{7}{6} : (\frac{32}{12} - \frac{21}{12}) = -\frac{7}{6} : \frac{11}{12} = -\frac{7}{6} * \frac{12}{11} = -\frac{14}{11} = -1\frac{3}{11}[/tex]
b)
[tex](1\frac{1}{2} - 3*1\frac{1}{3}) : 2\frac{1}{2} = (\frac{3}{2} - \frac{3}{1}*\frac{4}{3}) : \frac{5}{2} = (\frac{3}{2} - \frac{4}{1}) : \frac{5}{2} = (\frac{3}{2} - \frac{8}{2}) : \frac{5}{2} = - \frac{5}{2} : \frac{5}{2} = -1[/tex]
c)
[tex](3\frac{1}{2} + 5\frac{1}{3}) : 2\frac{1}{4} = (\frac{7}{2} +\frac{16}{3}) : \frac{9}{4} = (\frac{21}{6} + \frac{32}{6}) : \frac{9}{4} = \frac{53}{6} : \frac{9}{4} = \frac{53}{6}*\frac{4}{9}= \frac{53}{3} * \frac{2}{9} = \frac{106}{27}[/tex]
e)
[tex]\frac{1}{3} - \frac{6}{10}*\frac{12}{5}-\frac{4}{5}:\frac{1}{5}+4 = \frac{1}{3} - \frac{6}{5}*\frac{6}{5}- \frac{4}{5} * \frac{5}{1}+\frac{4}{1} = \frac{1}{3} - \frac{36}{25} - \frac{4}{1} + \frac{4}{1} = \frac{1}{3} - \frac{36}{25} = \frac{25}{75}-\frac{108}{75} = -\frac{83}{75}= -1\frac{8}{75}[/tex]
f)
[tex](-\frac{5}{12} + 2\frac{4}{15})*(-45) = (-\frac{5}{12} +\frac{34}{15})*(-45) = (-\frac{25}{60}+\frac{136}{60})*(-45)= \frac{111}{60}*(-\frac{45}{1})= \frac{111}{4}* (-\frac{3}{1})=-\frac{333}{4}[/tex]
g)
[tex]3\frac{3}{4} * 1\frac{1}{5} + (-1\frac{1}{2}):2\frac{2}{5}-\frac{1}{4} = \frac{15}{4}*\frac{6}{5}-\frac{3}{2}:\frac{12}{5}-\frac{1}{4}=\frac{3}{2}*\frac{3}{1}-\frac{3}{2}*\frac{5}{12}-\frac{1}{4} =\frac{9}{2}-\frac{1}{2}*\frac{5}{4} -\frac{1}{4}= \frac{9}{2}-\frac{5}{8}-\frac{1}{4}= \frac{36}{8}-\frac{5}{8}-\frac{2}{8} = \frac{29}{8}[/tex]
Powodzenia ;)